Economic impact analysis of inland waterway disruption response. Issue 1 (2nd January 2017) - Oztanriseven, Furkan; Nachtmann, Heather
ABSTRACT: Navigable inland waterways connect inland ports with the global supply chain by providing a low-cost, reliable, and environmentally friendly freight transportation mode. In this article, we present the results from a simulation-based approach that estimates the potential economic impacts of inland waterway disruption response. Predicting economic impacts of inland waterway disruption response enables system stakeholders to increase their preparedness and potentially reduce economic losses. Our approach is implemented on an illustrative case study of the McClellan–Kerr Arkansas River Navigation System. The approach is generalizable to navigable inland waterways throughout the United States to support economic resilience of these systems.